Folkcommunicational Agents and Collective Memory: Organizing the Territory from the Popular Experience (Revista Internacional de Folkcomunicação, 2020)
This article is part of an ongoing research developed at the foothills of Región de Los Ríos, Chile, where former inhabitants seek to recover territory of the former Panguipulli Forestry and Timber Complex (COFOMAP) from where they were forcefully displaced during the military dictatorship (1973-1989). The objective is to analyse the stakeholders’ folkcommunicational practices that grant meaning to the land ownership from the popular culture, which emerges as the collective memory and strengthens the organization. This dimension was identified from the fieldwork that included group interviews and participant observation. Thus, a corporate plundering resistant narrative is articulated and the vivid state terrorism grant intelligibility to the current struggle and the demands for justice. Collective Memory; State Terrorism; Folkcommunicational Practices; Forced Displacement.